Determining proficiency level in foreign language teaching: the case of translation and interpretation students - Celik, Pinar Guzelyurek; Ozcan, Lale Arslan (ELSEVIER SCIENCE BV, 2013)
The aim of our article is to investigate to what extent the existing foreign language level determination systems are adaptable to translation and interpretation student profile. We also aim to underline the proficiency level differences and question what type of studies can be done on students' foreign language level differences. Unlike The Common European Framework of Reference (CEFR), which is accepted as a core stone in foreign language teaching, there is an officially recognized reference system based on active language and passive language in education of translation and interpretation, particularly conference interpreting. (C) 2012 Published by Elsevier Ltd.
Keywords: The Common European Framework of Reference (CEFR); active language; passive language; education of translation and interpretation; education of conference interpreting; Education & Educational Research; Linguistics